Root exudate fingerprint of Brachiaria humidicola reveals vanillin as a novel and effective nitrification inhibitor - Egenolf, Konrad; Schöne, Jochen; Conrad, Jürgen; Braunberger, Christina; Beifuß, Uwe; Arango, Jacobo; Rasche, Frank (Frontiers in Molecular Biosciences, 2023)
Biological Nitrification Inhibition (BNI) is defined as the plant-mediated control of soil nitrification via the release of nitrification inhibitors (Subbarao et al. 2006). BNI of Brachiaria humidicola (syn. Urochloa humidicola) has been mainly attributed to root-exuded fusicoccane-type diterpenes, e.g. 3-epi-brachialactone. We hypothesized, however, that BNI of B. humidicola is caused by an assemblage of bioactive secondary metabolites. B. humidicola root exudates were collected hydroponically, and metabolites were isolated by semi-preparative HPLC. Chemical structures were elucidated by HRMS as well as 1D and 2D NMR spectroscopy. Nitrification inhibiting potential of isolated metabolites was evaluated by a Nitrosomonas europaea based bioassay. Besides previously described brachialactone isomers and derivatives, five phenol and cinnamic acid derivatives were identified in the root exudates of B. humidicola: 2-hydroxy-3-(hydroxymethyl)benzaldehyde, vanillin, umbelliferone and both trans-and cis-2,6dimethoxycinnamic acid. Notably, vanillin revealed a substantially higher nitrification inhibiting activity than 3-epi-brachialactone (ED50 12.5 µg ml -1 , ED80 20 µg ml -1 ), identifying this phenolic aldehyde as novel nitrification inhibitor (NI). Furthermore, vanillin exudation rates were in the same range as 3-epi-brachialactone (1-4 µg h -1 g -1 root DM), suggesting a substantial contribution to the overall inhibitory activity of B. humidicola root exudates. In relation to the verification of the encountered effects within soils and considering the exclusion of any detrimental impact on the soil microbiome, the biosynthetic pathway of vanillin via the precursor phenylalanine and the intermediates p-coumaric acid / ferulic acid (precursors of further phenolic NI) might constitute a promising BNI breeding target. This applies not only to Brachiaria spp., but also to crops in general, owing to the highly conserved nature of these metabolites.